Extracellular vesicles epitopes as potential biomarker candidates in patients with traumatic spinal cord injury - Jason-Alexander Hörauf; Cora Rebecca Schindler; Inna Schaible; Minhong Wang; Birte Weber; André El Saman; Christiane Pallas; Marek Widera; Ingo Marzi; Dirk Henrich; Liudmila Leppik (Frontiers in Immunology)
BackgroundExtracellular vesicles (EVs), a heterogeneous group of cell-derived, membrane-enclosed vesicles bearing cell-specific epitopes, have been demonstrated to play a crucial role in neuronal-glial communication and the orchestration of neuroinflammatory processes. However, the existing evidence regarding their function as biomarkers and their role in the pathobiology of traumatic spinal cord injuries (tSCI), particularly in humans, is scarce.ObjectiveThe primary goal of this study was to investigate whether a distinct pattern of EV surface epitopes detected in the plasma of individuals suffering from spinal cord injury is indicative of tSCI.MethodsThe study includes patients with isolated tSCI (n=8), polytrauma patients without tSCI (PT; ISS ≥16, n=8), and healthy volunteers (HV; n=8). Plasma samples from tSCI and PT patients were collected right after admission to the emergency room (ER), 24 hours (24h), and 48h after trauma. EVs were isolated via size exclusion chromatography, and EVs’ surface epitopes were quantified with MACSPlex EV Kit Neuro (prototype product, Miltenyi Biotec) and compared among the groups. Additionally, results were correlated with clinical parameters.ResultsIn total, 19 epitopes differed significantly between the tSCI and the HV groups. Out of these 19, four (CD47, CD56, CD68, and ADAM17) were found to differ significantly among tSCI and PT groups. The expression of the CD47 epitope was found to correlate positively with the American Spinal Injury Association (ASIA) impairment scale.ConclusionWe identified four potential EV-based tSCI biomarkers (CD47+, CD56+, CD68+, and ADAM17+ EVs) that differ in tSCI, with CD47+ EVs showing a strong correlation with the neurological function in tSCI. Thus, future studies might further specify the relevance of potential tSCI-specific biomarkers and investigate underlying mechanisms of tSCI.